The problem of related verbs in mental lexicon - Anastasia Chuprina (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2019)
Memory of a person contains various kinds of information about the word and its link to related words. To the topical (in terms of functioning) information pertains the unity, full or partial, of their phonological and morphemic set-up, similarity of morphological features, semantic properties and syntactic behaviour. What is more important for the storage of the interrelated group and access to it: formal or semantic link between the units? Results of psycholinguistic studies are classifi ed into those which testify to the equal signifi cance of the form and meaning of related words for the topicalisation of information in mental lexicon and those according to which it is only the formal processing of the word that takes place during the access to the mental representation of the word. Based on the material of a group of Russian verbs and their prefi xed and suffi xed derivatives, this article studies which general information is more important for the lexical access to the primary word in the Russian language, i. e. the structural similarity of the verb with its prefi xed derivative or predictability of the change in semantics as to the suffi xed derivative. A psycholinguistic experiment employing the technique of morphological priming has been conducted. Its results have shown that the predictability of semantics is more important in accessing the representation of the primary verb in memory. The experiment has shown that even a short-time activisation of the suffi xed derivative before reading the primary verb is suffi cient for this verb to be recognised faster than in the case of preliminary activisation of the prefi xed verb. This leads to the conclusion that regular and predictable modifi cations in the sense are more important for the arrangement of related words than their shared phonological and morphological features.